PSYCHOEMOTIONAL STRESS AS A FACTOR AFFECTING NEUROENDOCRINE MECHANISMS IN ADOLESCENT GIRLS (Web of Teachers: Inderscience Research, 2024)
Adolescence is characterized by significant changes in the activity of the nervous and endocrine systems. At this age, psychoemotional stress can affect the hormonal background and the development of sexuality, causing neuroendocrine disorders. The article analyzes the mechanisms of stress on the hypothalamic-pituitary-adrenal system (GGAT), neuroplasticity of the brain, as well as methods of correcting such conditions. The data of modern studies showing the role of social and biological factors in these processes are presented.